Correlations among carcass traits taken by ultrasound and after slaughter in Mediterranean (Bubalus bubalis) young bulls - Jorge, Andre Mendes [UNESP]; Andrighetto, C. [UNESP]; de Lima Francisco, C. [UNESP]; de Amorim Ramos, A. [UNESP]; Bonilha Pinheiro, R. S. [UNESP]; Rodrigues, E. [UNESP] (Pagepress Publ, 2007)
The objective of this work was to estimate the correlations among measurements taken in vivo with ultrasound equipment with some carcass traits measured after slaughter. Twenty eight Mediterranean bulls, with average shrunk body weight of 330 kg and 14 months of age, were fed by 120 days with high concentrate diets. The shrunk body weight, the ribeye area (REAU), the back fat thickness (FTU) over the Longissimus dorsi muscle between 12(a) and 13(a) ribs and rump fat (EGP8U), were measured at 28 days intervals. Real-time ultrasound equipment Piemedical Scanner 200 VET, with 18 cm linear array transducer was utilized. After the slaughter, the hot carcass weight (PCQ) and the kidney, pelvic and inguinal fat (GRPI) were weighted and the dressing percentage (DP) calculated. After 24 hours of cooling the ribeye area (REAC), backfat thickness (FTC) and rump fat (EGP8C) were measured. Both the REAC, FTC and EGP8C were underestimated by ultrasound measurements. The Pearson correlation coefficients for ribeye area, backfat thickness and rump fat measured in the carcass and with ultrasound, were 0.96, 0.99 and 0.91, respectively. The coefficient between DP and REAU was 0.47; 0.45 between DP and REAC, 0.56 between DP and FTU and 0.58 between DP and FTC. DP presented a 0.59 correlation coefficient with EGP8U. The Spearman correlation was estimated between REAU and REAC, FTU and FTC, EGP8U and EGP8C, and the values were 0.96, 0.99 and 0.91,respectively. The ultrasound measures could be used to estimate carcass traits in buffaloes with good accuracy.
Keywords: Buffaloes; Carcass traits; Ultrasound evaluation